Função física pré e pós-operatória de pacientes submetidos à cirurgia cardíaca - Real, Amanda Albiero (2017)
The discussion about functional scales in the hospital environment is currently increasing, and new measures for the evaluation of physical function and mobility status have been developed specifically for use in Intensive Care Units (ICUs). In this context, the Perme Intensive Care Unit Mobility Score (Perme Score) has been shown to be a reliable tool to the evaluation of physical function and of mobility status of patients admitted to the Cardiology Intensive Care Unit (CICU) and can be an important tool for clinical practice. However, there are few studies using such instrument in Brazil. In addition, in the published studies involving Perme Score, it was applied only at a specific time of hospitalization in different patient profiles and had not yet been applied as a daily follow-up of the mobility status of CICU patients. Based on this assumption, in the present prospective observational study, the Perme Score was daily collected to evaluate the postoperative (PO) mobility status of patients undergoing elective coronary artery bypass graft surgery (CABG) and / or valve replacement during their stay in the CICU of the Hospital Universitário de Santa Maria (HUSM). The study included 44 patients of both sexes, over 18 years of age, admitted to the HUSM with indication of CABG and / or valve replacement surgery. In addition to the daily evaluation of the mobility status of patients in the CICU through Perme Score, the following preoperative evaluations were performed: pulmonary function, respiratory muscle strength (RMS) and handgrip strength (HGS), which were repeated in the CICU discharge. Pulmonary function was measured through spirometry, RMS through manovacuometry and HGS through handgrip dynamometry. The results demonstrated that there was a gradual increase in the mobility status of patients in PO of cardiac surgery during their hospitalization, culminating in their best performance in Perme Score in the CICU discharge. In addition, a reduced CICU length of stay was observed in patients who presented a better mobility status on the 2nd as well as in the 3rd day of PO, observed through high scores in Perme Score. However, there was a significant reduction of all variables of pulmonary function, RMS and HGS when comparing preoperative with post- CICU discharge evaluations. It was concluded that Perme Score was able to objectively measure the daily mobility status of patients after cardiac surgery during their entire stay in the CICU. The results of the study suggest that a higher mobility status may be related to the reduction of CICU stay time. These findings aim to contribute to the implementation of Perme Score as a routine in these units, as well as to increase the levels of scientific evidence related to ICU-specific functional scales, and to the physical function and mobility status of patients in the PO period of cardiac surgery during CICU stay.